ANALISIS BIOAUTOGRAFI DAN KARAKTERISASI DENGAN FTIR PADA FRAKSI DAUN LABU SIAM (Sechium edule (jacq).SW) TERHADAP Porphyromonas gingivalis DAN Streptococcus mutans - Laila Susanti; Isbiyantoro Isbiyantoro; Septiana Simanjuntak (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
Siamese pumpkin leaves are one of the plants that have antibacterial properties. Compounds that act as antibacterial are flavonoite, tannin, triterpenes, alkaloids, and saponins. The aim of this study was to prove the antibacterial activity of ethanol hexane and chloroform fraction of pumpkin siam leaves and characterize the functional groups of active compounds from pumpkin siam leaves (Sechium edule (jacq). SW) with FTIR spectrophotometers. The extraction process of Siamese Pumpkin leaves was carried out by maceration method using 70% ethanol. The extract was continued with the fractionation process with ethanol, n-hexane and chloroform solvents. Antibacterial activity testing using the well method with a concentration of 100%, positive control chlorhexidi and negative control aquadst. The compound content test used the Thin Layer Chromatography (TLC) method with the stationary phase using silica plate G60 F254 and comparison of the mobile phase of chloroform: methanol: water (2: 5: 3) (v / v). Bioautography test using the contact method, namely the elution TLC plate, was placed on the NA medium containing a bacterial suspension for 3 hours. Antibacterial test results The largest ethanol fraction of pumpkin leaves was at a concentration of 100% with a diameter of inhibition zone of 11.49 mm on P. gingivalis while 16.04 mm in S. mutans. The results of TLC showed the presence of flavonoids with a price of Rf 0.47 and tannin with a price of Rf 0.84. Bioautography results showed a inhibition zone with a price of Rf 0.49 in the bacteria P. gingivalis and S. mutans which are flavonoid compounds. Characterization by FTIR spectrophotometer O-H phenol, C = C aromatic, C-O-C ether, aromatic C-H functional group Keywords: (Sechium edule (jacq) .SW). Porphyromonas Gingivalis, Streptococcus mutans, TLC, Bioautography and FTIR